Bleeding is associated with intravenous immunoglobulin and therapeutic plasma exchange use in heparin‐induced thrombocytopenia: A propensity matched analysis. Issue 3 (7th May 2021) - Soares Ferreira Júnior, Alexandre; Boyle, Stephen H.; Kuchibhatla, Maragatha; Onwuemene, Oluwatoyosi A.
Abstract: Intravenous immunoglobulin (IVIG) and therapeutic plasma exchange (TPE) are used in select cases with heparin‐induced thrombocytopenia (HIT). In a cross‐sectional analysis, a propensity matched sample was generated by IVIG or TPE treatment status to assess the primary outcome of mortality. In 500 HIT cases, IVIG or TPE was not associated with increased mortality (OR = 1.46; 95% CI: 0.81–2.63, p  = 0.2052) but was associated with a higher likelihood of major bleeding (OR = 1.75; 95% CI: 1.03–2.96, p  = 0.0376). The use of IVIG or TPE in HIT cases with bleeding contraindications to standard therapies should be further investigated.